Navigating ethical waters: The impact of ethical judgment, norms, and CSR skepticism on CSR engagement and purchasing intention in a breast cancer campaign - Yang Cheng; Yangzhi (Nicole) Jiang; Qizhao Zhang (PLoS ONE, 2026)
Corporate social responsibility (CSR) campaigns play a crucial role in shaping consumer perceptions and behavior. This study examines Delta Air Lines’ CSR campaign centered on breast cancer awareness, focusing on how ethical judgment and subjective norms are associated with CSR skepticism and how such skepticism, in turn, relates to CSR engagement and ethical purchasing intention. Drawing on the theory of reasoned action (TRA), a quantitative survey was conducted with 787 Delta Air Lines customers, all of whom provided informed consent prior to participation. The data, analyzed between August 1–7, 2024 using structural equation modeling, show that ethical judgment and subjective norms are associated with lower levels of CSR skepticism. In turn, CSR skepticism is negatively related to both CSR engagement and ethical purchasing intention, while higher levels of CSR engagement are associated with greater ethical purchasing intention. These findings provide insight into the role of ethical and social factors in shaping consumer responses to CSR initiatives and highlight the importance of fostering engagement to enhance the effectiveness of CSR campaigns and promote favorable consumer outcomes.